Pelatihan Komputer Bagi Kader PKK Desa Kaibon - Pambudi, Mijan; Susmiyanto, Susmiyanto; Firharmawan, Hastri (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Family Welfare Empowerment or often shortened to PKK is a movement that has been built from the center to the village and its existence and benefits have been felt by the community. This PKK activity is reflected in the 10 PKK Main Programs, one of which isthe program focuses on health and special attention is paid to the health of mothers and children. These trained PKK cadres are not only seen from the way they handle maternal and child health but also must be supported by their ability to use computers in the recording and data collection process. However, not all PKK Cadres, especially in villages, are proficient in using computers, for example, PKK Cadres in Kaibon Village. In fact, many cadres are new to computers and cannot use standard programs such as Microsoft Excel and Microsoft Word. Kaibon Village PKK Cadres in operating computers to support good and smooth performance in terms of administration and data collection.Keywords: Computer Training, Kaibon Village PKK cadres